1998
DOI: 10.1128/aac.42.10.2564
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Inhibitory and Bactericidal Activities and Postantibiotic Effects of LY333328 and Ampicillin Used Singly and in Combination against Vancomycin-Resistant Enterococcus faecium

Abstract: One hundred ninety-five individual vancomycin-resistant Enterococcus faecium (VRE) isolates from five upstate New York hospitals were studied for antimicrobial susceptibilities to LY333328, quinupristin-dalfopristin, teicoplanin, ampicillin, and gentamicin. LY333328 was the most active antibiotic against VRE. The effect of media and methods on the antibacterial activity of LY333328, its synergy with ampicillin, and the postantibiotic effects (PAE) of LY333328 and ampicillin were evaluated. In microdilution tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 28 publications
0
41
0
1
Order By: Relevance
“…Conflicting results are reported from several studies. Synergy with ampicillin, quinupristin dalfopristin and gentamicin was shown in an in vitro study against vancomycin-resistant E. faecium [119] . In another in vitro study, synergy with ciprofloxacin was also demonstrated against E. faecalis [121] .…”
Section: Synergy: In Vitro Datamentioning
confidence: 98%
See 3 more Smart Citations
“…Conflicting results are reported from several studies. Synergy with ampicillin, quinupristin dalfopristin and gentamicin was shown in an in vitro study against vancomycin-resistant E. faecium [119] . In another in vitro study, synergy with ciprofloxacin was also demonstrated against E. faecalis [121] .…”
Section: Synergy: In Vitro Datamentioning
confidence: 98%
“…The PAE of oritavancin is not fully investigated yet; recent data support that it is concentration dependent and seems to be longer in staphylococci and enterococci compared with other Gram-positive pathogens [119] . In an early in vitro study testing oritavancin against VRE isolates, the PAE of oritavancin was prolonged (23 h at 10-times the MIC).…”
Section: Postantibiotic Effectmentioning
confidence: 98%
See 2 more Smart Citations
“…A synergistic effect against vancomycin-resistant Enterococcus faecalis is produced when oritavancin is added to gentamicin [21]. Combinations with ampicillin, quinupristin/dalfopristin and gentamicin are synergistic against vancomycin-resistant Enterococcus faecium [22].…”
Section: Antimicrobial Activitymentioning
confidence: 99%